Agro-innovation – path to agricultural entrepreneurship: feasibility study / Elias Kamaruzzaman … [et al.] - Kamaruzzaman, Elias; Mohd Daud, Norzaidi; Wahab, Samsudin; Abu Dardak, Rozhan (Universiti Teknologi MARA, Shah Alam, 2019)
Technology changes will always be for the better, not only to the end users but also to the intellectual property owners of the technology and the implementers of the technology. The objective of this paper is to study the feasibility and viability for entrepreneurs to become service providers for the dispensation of fertilizers, pesticides, fungicides and supporting services such as aerial crop reconnaissance using Unmanned Aerial Vehicles (UAV) or drones. The methodology used for this study is SWOT Analysis. Both primary and secondary data is used for this analysis. This study finds that paddy farming employing drones is feasible. The beneficiaries of this study shall be the government, by way of lowering financial cost to subsidise the paddy planting, the farmers who no longer need the services of migrant workers, thus saving production cost, and finally the drone service providers and their downstream business associates who can engaged themselves in very lucrative businesses.